FISCAL POLICY AS THE BASIS OF A COUNTRY'S FINANCIAL STABILITY (International Conference on Modern Science and Scientific Studies, 2025)
This article examines the cash accounting system in enterprises and the need to improve it in accordance with modern requirements and International Financial Reporting Standards (IFRS). Special attention is given to the accurate presentation of cash flows and the clear separation of operating, investing, and financing activities. The article also analyzes existing issues in national accounting practices and proposes solutions based on international approaches. The study provides practical recommendations for enhancing cash accounting transparency, strengthening financial control, and creating a reliable information base for investors.